2002
DOI: 10.1056/nejmoa012643
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Mycobacterial Furunculosis Associated with Footbaths at a Nail Salon

Abstract: We identified a large outbreak of rapidly growing mycobacterial infections among persons who had had footbaths and pedicures at one nail salon. Physicians should suspect this cause in patients with persistent furunculosis after exposure to whirlpool footbaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(130 citation statements)
references
References 13 publications
1
114
2
5
Order By: Relevance
“…These have included alcohol-tattoo ink contaminated with M. chelonae 368 and footbaths in nail salons contaminated with NTM spp. 369 Summary. Most potential sources of pathogens that have been identified in the healthcare environment can be eliminated by following facility processes for the cleaning and disinfection of surfaces and equipment.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
“…These have included alcohol-tattoo ink contaminated with M. chelonae 368 and footbaths in nail salons contaminated with NTM spp. 369 Summary. Most potential sources of pathogens that have been identified in the healthcare environment can be eliminated by following facility processes for the cleaning and disinfection of surfaces and equipment.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
“…In contrast, NTM infections in immunocompetent hosts are often localized, such as SSTIs. Healthcare-associated or postsurgical wound infections caused by RGM have often been reported as SSTIs [1,[5][6][7][8]. The clinical presentation includes cellulitis, abscess formation, draining sinuses, and postoperative wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic drugs usually recommended for infections involving the M. fortuitum group include amikacin, cefoxitin, imipenem/cilastatin, and fluoroquinolones [13]. In a study of isolates from a large nail salon outbreak of SSTIs, 29 isolates were susceptible to amikacin (100%), ciprofloxacin (100%), minocycline (100%), cefoxitin (91%), doxycycline (89%), gentamicin (82%), and trimethoprimsulfamethoxazole (TMP-SMX) (61%), with intermediate susceptibility to clarithromycin (86%) [5,16]. However, a study from Taiwan reported a high prevalence of antimicrobial resistance in RGM including the M. fortuitum group (69 isolates), and amikacin was found to be the most active agent (100% susceptibility).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha identifi cado al lavado de pies en lugares comunitarios durante un proceso de pedicuría, como un sitio de brote de forunculosis asociada a M. fortuitum 14,15 .…”
Section: Discussionunclassified